MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN KOLASE - Rizki rizki Savitri (UNIVERSITAS PGRI MADIUN, 2022)
ABSTRACTThe purpose of this study was to find out and obtain information about improving fine motor aspects in early childhood through collage activities with various media, the object in group B of Az Zaini Kebalen Kindergarten, Babelan District, Bekasi Regency consisted of 8 girls and 7 boys. This type of Classroom Action research with the Kemmis Taggart model, consists of 2 cycles, each cycle has 4 stages, namely observation, planning, implementation and observation/reflection, data collection techniques through observation. The results showed that the ability of the fine motor aspect with collage activities in the initial conditions of 58% the category began to develop after the first cycle increased to 86.67% children developed as expected and after the second cycle the average development of the fine motor aspect reached 100% category Fine motor skills are very well developed.Keywords: fine motor skills, collage activities